A case report and literature review: pheochromocytoma-mediated takotsubo cardiomyopathy, which is similar to acute myocardial infarction - Zhang, Zhiyu; Guo, Xia; Wang, Jingyue; Wang, Shipeng; Wang, Yushi (Frontiers in Cardiovascular Medicine, 2023)
A 52-year-old Chinese woman was admitted to a cardiac intensive care unit (CCU) due to nausea, vomiting, and dyspnea, which began a day before her hospitalization. Metoprolol succinate and conventional treatment for acute myocardial infarction (AMI) were initially administered to the patient based on electrocardiogram (ECG) findings and elevated cardiac troponin I (cTnI). However, the following day, she developed aggravated nausea, vomiting, fever, sweating, a flushed face, a rapid heart rate, and a significant rise in blood pressure. Furthermore, ultrasonic cardiography (UCG) displayed takotsubo-like changes; nevertheless, ECG indicated inconsistent cTnI peaks with extensive infarction. After coronary computed tomography angiography (CTA) ruled out (AMI), and in conjunction with the uncommon findings, we strongly suspected that the patient had a secondary condition of pheochromocytoma-induced takotsubo cardiomyopathy (Pheo-TCM). In the meanwhile, the use of metoprolol succinate was promptly discontinued. This hypothesis was further supported by the subsequent plasma elevation of multiple catecholamines and contrast-enhanced computed tomography (CECT). After one month of treatment with high-dose Phenoxybenzamine in combination with metoprolol succinate, the patient met the criteria for surgical excision and successfully underwent the procedure. This case report demonstrated that pheochromocytoma could induce TCM and emphasized the significance of distinguishing it from AMI (in the context of beta-blocker usage and anticoagulant management).